Don't bump the glump! : and other fantasies - Silverstein, Shel. (New York : HarperCollins, 2008)
A collection of fun poems for children by Shel Silverstein featuring unusual, silly, and scary creatures.
3.2
K-3
Keywords: Children's poetry, American; Humorous poetry, American; American poetry; Humorous poetry; American poetry; Humorous poetry